Design of a testing device for an anatomical part of the ascending aorta - Castanho, Francisco Luís Mathiotte (2021)
Aortic aneurysms are life-threatening pathologies that cause thousands of deaths worldwide. The current main clinical criteria for surgical intervention is aortic diameter, although a large percentage of patients with dissection or rupture has a normal diameter. Computation methods have been adopted to model the biomechanical behaviour of biological tissue in view of adding in the diagnosis of this pathology. Furthermore, experimental testing on aneurismatic aortic tissue has been performed to validate these models. The objective of this study is to integrate com- putational mechanical methods into an innovative experimental test with a specifically designed device where material parameters are obtained by inverse methods assisted by Digital Image Correlation (DIC). Axiomatic Design (AD) is taken into consideration to develop the testing device in a clear, methodical, and efficient way. A case study is analysed, and a patient-specific 3D geometry of an Ascending Thoracic Aortic Aneurysm (ATAA) is obtained by segmenting Computed Tomography Angiography (CTA) images. A methodology is presented by attribut- ing a hyperelastic constitutive model to the geometry and executing Finite Element Analysis (FEA). Future work should rely on real experimental tests where Finite Element Model Up- dating (FEMU) should be adopted to fit the constitutive model more accurately to the actual specimen material.